Prediksi Angka Harapan Hidup di Indonesia Berdasarkan Jenis Kelamin Menggunakan Regresi Linear - Nisa, Khoirun; Susianto, Anisya Septianur; Syahfitri, Daira; Rahayuningtyas , Dian; Aulia, Elsya Bani (Jurnal Ilmiah Media Sisfo, 2025)
This study discusses the prediction of Life Expectancy (LE) in Indonesia based on gender for the period 2025 to 2029. LE is used as an indicator of societal welfare and quality of life. Historical data on male and female LE were obtained from the Central Bureau of Statistics and analyzed using the linear regression method. This research aims to identify the growth patterns of LE separately by gender. The regression model was developed by segregating the data based on gender, followed by model training, accuracy evaluation using the coefficient of determination, and analysis of the prediction results. This method produces a predictive model that can be utilized in the formulation of medium-term health policies. The study contributes to the development of a simple statistical model for LE projection specifically by gender, which has been rarely addressed in previous studies.